INTEGRATIVE ANALYSIS OF LONGITUDINAL CHANGES OF NEUROPSYCHOLOGICAL TESTS IN LONG LIFE FAMILY STUDY PARTICIPANTS. (11th November 2018) - Sebastiani, P; Andersen, S L; Sweigart, B; Cosentino, S; Thyragajan, B; Schupf, N; Christiansen, K; Perls, T T
Abstract: We used Bayesian latent-group growth modelling to identify patterns of cognitive decline among Long Life Family participants in the domains of episodic memory, attention, processing speed and verbal fluency. For each neuropsychological test, we identified 4 or 5 large clusters of participants characterized by a 10% to 80% loss of the initial score. We conducted an extensive "annotation analysis" of the clusters with genetic and molecular biomarkers, non-genetic risk factors, medical history, and other markers of aging. This analysis discovered predictors of multi-domain cognitive change such as gait speed and domain-specific predictors of cognitive change, for example low IL6 and NTproBNP predict slower change of processing speed (p-value<0.0006). Comparison of clusters of different tests indicated agreement ranging from 35% to 50%. This analysis shows the importance of measuring a range of cognitive functions and the need for a wide net of risk factors to monitor cognitive health of aging individuals.